The impact of endolymphatic hydrops on wideband acoustic immittance and otoacoustic emissions in guinea pigs - Huan Lin; Xuanyi Li; Huiying Zhang; Yi Mu; Xi Wang; Naveena Konduru; Renlong Ji; Wen Liu; Wen Liu; Wen Liu; Zhao Fei; Wen Jiang; et al. (Frontiers in Neurology)
BackgroundInner ear disorders, such as EH, commonly lead to hearing loss and vestibular dysfunction. EH is particularly prevalent in various inner ear diseases, including Meniere’s disease. We aimed to evaluate the effects of EH on WAI and OAEs.ObjectiveThis study explores the potential of wideband acoustic immittance (WAI) and otoacoustic emissions (OAEs) for the early detection of changes in acoustic transmission associated with vasopressin-induced endolymphatic hydrops (EH) in a guinea pig model.MethodsWe induced EH in guinea pigs via daily intraperitoneal injections of arginine vasopressin over 14 consecutive days. Auditory function was assessed using Auditory Brainstem Responses (ABR), while changes in sound energy transmission were measured using WAI and Distortion Products Otoacoustic Emissions (DPOAE).ResultsIncreased ABR thresholds in EH models were statistically significant (p < 0.05). After 14 days of EH induction, absorbance at 1 kHz significantly increased, whereas it significantly decreased at 4 kHz and 6 kHz (p < 0.05). DPOAE measures, both magnitude and phase, showed no significant changes (p > 0.05).ConclusionWAI demonstrates greater sensitivity than DPOAE in the early detection of acoustic transmission alterations in EH models, suggesting its utility as a diagnostic tool in early-stage inner ear disorders.